Dlaczego Abraham uwierzył Bogu (Rdz 15,6)? - Lemański, Janusz (Verbum Vitae, 2004)
Having seen prophesy of the Promised Land been fulfilled (Gen 12-14), Abraham experienced the faith crisis due to a lack of offspring. Yet once again he answered with trust in the Word o f God, and i t bas been reckoned to him for righteousness (Gen 15,6). The following chapters (Gen 16-22) present the fulfillment of the promise o f heir. The faith of Abraham will come to perfection at the trial, as it is seen in Gen 22. In sucha context, words o f the narrator in Gen 15,6 are the turning point in the growth of his faith.